10.1016/s1553-3212(08)70186-9 (CrossRef Listing of Deleted DOIs, 2000)
Aim Risk assessment tools for periodontitis lack sufficient precision to predict disease progression. The aim of this exploratory study was to evaluate proteolytic activity (PA) in gingival crevicular fluid in relation to clinically assessed progression risk, microbial community composition and host proteome. Materials and methods Samples were collected from 109 patients with periodontitis and stratified into high and low PA groups using a fluorescent substrate. Microbial composition was analysed via 16S rRNA gene sequencing, and host proteomic profiles were determined using mass spectrometry. Results Forty-one of 42 patients in the high PA group were clinically classified as high-risk, while the low-activity group included both low- and high-risk individuals. High-activity samples displayed greater microbial diversity and enrichment of proteolytic species including Fusobacterium nucleatum, Porphyromonas gingivalis and Treponema denticola. Of the 235 differentially expressed host proteins, high-activity samples had elevated markers of inflammation and neutrophil-mediated immunity, whereas low-activity samples were enriched in protease inhibitors, indicating more effective regulation of tissue degradation. Conclusions Small-volume gingival crevicular fluid sampling allows integrated analysis of microbial and host signatures that provide insight into the pathobiology of periodontitis. PA stratifies patients according to these microbial and host proteome signatures.